Network Pharmacology and Experimental Validation to Explore the Mechanism of Qing-Jin-Hua-Tan-Decoction Against Acute Lung Injury - Xiao, Shunli; Liu, Lu; Sun, Zhengxiao; Liu, Xiaoqian; Xu, Jing; Guo, Zhongyuan; Yin, Xiaojie; Liao, Fulong; Xu, Jun; You, Yun; Zhang, Tiejun (Frontiers in Pharmacology, 2022)
Qing-Jin-Hua-Tan-Decoction (QJHTD) a classic famous Chinese ancient prescription, has been used for the treatment of pulmonary diseases since Ming Dynasty. 22 prototype compounds of QJHTD absorbed into rat blood were chosen as candidates for the pharmacological network analysis and molecular docking. The targets from the intersection of compounds’ target and ALI disease targets were used to GO and KEGG enrichment analysis. Molecular docking was adopted to further verify the interactions between 22 components and the top 20 targets with higher degree values in the component-target-pathway network. In vitro experiments were performed to verify the results of network pharmacology using SPR experiments, western blot experiments and PMA-induced neutrophils produce neutrophil extracellular traps (NETs) model. The compounds-target-pathway network includes 176 targets and 20 signaling pathways in which the degree of MAPK14, CDK2, EGFR, F2, SRC and AKT1 is higher compared with other targets and which may be the potential disease targets. The biological processes in which QJHTD for ALI mainly included protein phosphorylation, response to wounding, response to bacterium, regulation of inflammatory response and so on. KEGG enrichment analyses revealed multiple signaling pathways, including lipid and atherosclerosis, HIF-1 signaling pathway, renin-angiotensin system, neutrophil extracellular trap formation. The molecular docking results showed that baicalin, oroxylin A-7-glucuronide, hispidulin-7-O-β-D-glucuronide, wogonoside, baicalein, wogonin, tianshic acid, and mangiferin can be combined with most of the targets, which might be the core components of QJHTD in treatment of ALI. Direct binding ability of baicalein, wogonin, and baicalin to thrombin protein were all micromolar, and their KD values were 11.92 μM, 1.303 μM, and 1.146 μM respectively revealed by SPR experiments and QJHTD was able to inhibit Src phosphorylation in LPS-activated neutrophils by western blot experiments. The experimental results of PMA-induced neutrophils to produce NETs indicated that QJHTD could inhibit the production of NETs. This study revealed the active compounds, effective targets and potential pharmacological mechanisms of QJHTD acting on ALI.